Women's participation in the terrorist network in the view of gender - Husnatul Hamidiyyah Siregar; Ulfah Nurfadhila; Wildana Wargadinata (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
This study focus on gender Islamic regarding women's involvement in terrorism networks in Indonesia. The approach of Islamic studies becomes a paradigm or point of view in understanding gender issues, especially terrorism in Indonesia. This study has some objectives. There are how the approach of gender in Islam is, how Islam and Terrorism, and how Islamic studies and women's participation in terrorism networks is. The design of this study uses a literature review. The results of this study indicate that humans (women and men) can perform their functions as khalÃ®fah, such as piety and not gender. The existence of Islam with the values of justice and equality greatly benefits to the oppressed and marginalized, especially women.